Spatial factors influencing the subjective well-being and happiness of juveniles in regional youth rehabilitation centers of Davao City and South Cotabato - Matanguihan, Bea D.; Pernes, Nory Loyd N. (2023)
This research addressed the lack of adequate rehabilitation facilities and individualized intervention programs for juvenile offenders in the Philippines, with a focus on promoting human flourishing and positive development. The study examined the relationship between the built environment of youth rehabilitation centers and residents' subjective well-being and happiness. Qualitative methods were employed, including survey questionnaires and thematic analysis, to assess juveniles' levels of subjective well-being and happiness. The spatial attributes of rehabilitation centers were evaluated through questionnaires, interviews, and visual surveys.Findings revealed areas that required improvement in Regional Rehabilitation Centers, such as recreation and activity spaces, education and learning spaces, accommodation, spiritual enhancement spaces, visitation areas, and the physical environment. Design guidelines based on subjective well-being and happiness were presented, emphasizing positive relationships, engagement, autonomy, self-esteem, personal growth, and liberty. Juveniles' perceptions and preferences within the facility demonstrated their awareness of the rehabilitation environment, with resident, social, and activity areas being most important.The research highlighted the influence of the built environment on juveniles' cognitive behaviors. By utilizing concepts of subjective well-being and happiness as positive interventions, the environment was altered to prevent negative behaviors and help develop necessary social and individual skills for success in an inclusive environment.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2023